2010
DOI: 10.1021/es1011516
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Surface Complexation of Dimethylarsinic Acid on Iron (Oxyhydr)oxides from ATR-FTIR Studies and Quantum Chemical Calculations

Abstract: The surface chemistry of methylated arsenicals with ubiquitous geosorbents and industrial catalysts is poorly understood. These arsenic compounds pose both a health and an environmental risk in addition to being a challenge to the energy industry. We report herein a detailed spectroscopic analysis of the surface structure of dimethylarsinic acid (DMA) adsorbed on hematite and goethite using attenuated total internal reflectance Fourier transform infrared spectroscopy (ATR-FTIR). Spectra of adsorbed DMA, DMA(ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 39 publications
8
58
0
Order By: Relevance
“…At pH 6, the Fe-oxyhydroxide surface is positively charged, and MMA is negatively charged (CH 3 AsO 3 - ). It has reported that DMA and As V can form outer-sphere complexes with Fe/Al-oxyhydroxides [26-27]. Due to the similar molecular structures between As V , MMA, and DMA, it is possible that MMA also forms outer-sphere surface complex on the Fe-oxyhydroxide surface, contributing to the high sorption.…”
Section: Resultsmentioning
confidence: 99%
“…At pH 6, the Fe-oxyhydroxide surface is positively charged, and MMA is negatively charged (CH 3 AsO 3 - ). It has reported that DMA and As V can form outer-sphere complexes with Fe/Al-oxyhydroxides [26-27]. Due to the similar molecular structures between As V , MMA, and DMA, it is possible that MMA also forms outer-sphere surface complex on the Fe-oxyhydroxide surface, contributing to the high sorption.…”
Section: Resultsmentioning
confidence: 99%
“…The assignment of the spectral components observed in Fig. 1 has been discussed in detail in our recent publication reporting adsorption mechanism of DMA [34]. Briefly, the assignment of the observed frequencies was based on comparison with the spectra of bulk DMA in the liquid (pK a = 6.1) and solid acid and salt phases [37], desorption kinetics due to chloride and phosphate anions, and aided by frequency calculations on geometry-optimized clusters of DMA-iron oxide clusters.…”
Section: Resultsmentioning
confidence: 99%
“…3a and b for p-AsA are expressed in molecule cm À2 and molar ratios units using constants reported earlier [35]. The validity of this approach to quantifying S DMA and S p-AsA from spectral data was verified by bulk measurements of surface coverage from analysis of total arsenic using inductively coupled plasma atomic emission spectroscopy (ICP-AES) [34,35]. The quantification approach reported herein has the advantage of being an in situ cost-effective method (no chemical digestion is needed to release bonded arsenic).…”
Section: Calculations Of Dma Surface Coverage On Porous Fe-(oxyhydr)omentioning
confidence: 95%
See 1 more Smart Citation
“…Small peaks at 793 cm -1 and 884 cm -1 were observed only in 2.0 g ZVI experiment, which were assigned to As-O-Fe complexes (Jia et al, 2007;Guan et al, 2008;Adamescu et al, 2010). The band at 1080 cm -1 was assigned to jarosite (Bigham and Nordstrom, 2000).…”
Section: Dynamics Of As and Fe Release During Realgar Dissolution Witmentioning
confidence: 90%